High Expression of Cancer-IgG Is Associated With Poor Prognosis and Radioresistance via PI3K/AKT/DNA-PKcs Pathway Regulation in Lung Adenocarcinoma - Yang, Xiongtao; Wang, Guohui; You, Jing; Gu, Runchuan; Xu, Xiaohong; Xu, Changdan; Wang, Hao; Zhao, Ruisong; Qiu, Xiaoyan; Zhu, Guangying (Frontiers in Oncology, 2021)
Background Lung adenocarcinoma (LUAD) is the dominant type of lung neoplasms, and radiotherapy is its mainstay treatment, yet poor prognosis caused by radioresistance remains problematic. Cancer-derived immunoglobulin G (cancer-IgG) has been detected in multiple cancers and plays important roles in carcinogenesis. This study aimed to demonstrate that cancer-IgG is associated with poor prognosis of LUAD and to identify its role in radioresistance. Methods Cancer-IgG expression was detected by immunohistochemistry from 56 patients with stage III LUAD and by western blot and immunofluorescence in LUAD cell lines and in a human bronchial epithelial cell line. The effects of cancer-IgG silencing on the proliferation and apoptosis of PC9 and H292 cells were evaluated by plate cloning and apoptosis assay; the effects of cancer-IgG silencing on DNA damage repair ability and radiosensitivity were evaluated by colony-forming assay, γH2AX immunofluorescence, and neutral comet assay. Finally, we used the protein phosphorylation microarray and western blot to explore mechanisms involving cancer-IgG that increased radioresistance. Results Cancer-IgG is widely expressed in stage III LUAD, and the overall survival and disease-free survival of patients with positive expression are notably lower than those of patients with negative expression, indicating the associations between cancer-IgG and poor prognosis as well as radioresistance. The expression of cancer-IgG in the four LUAD cell lines was located mainly on the cell membrane and cytoplasm and not in the normal lung epithelial cell. Knockdown of cancer-IgG in PC9 and H292 cells resulted in increased apoptosis and negatively affected cancer cell proliferation. After irradiation, silencing of cancer-IgG showed a decrease in colonies as well as increases in the Olive tail moment and γH2AX foci in nucleus, indicating that the knockdown of cancer-IgG resulted in a decrease in the damage repair ability of DNA double-strand breaks in LUAD cells and an enhanced radiosensitivity. The expression of p-AKT, p-GSK3β, and p-DNA-PKcs decreased in the knockdown group after radiotherapy, suggesting that cancer-IgG could affect radiotherapy resistance by mediating double-strand breaks damage repair in LUAD cells through the PI3K/AKT/DNA-PKcs pathway. Conclusions This study revealed that cancer-IgG regulates PI3K/AKT/DNA-PKcs signaling pathways to affect radioresistance of LUAD and associated with poor prognosis.